The role of Islam in strengthening Kurdish national identity: a descriptive and analytical study - Palani, Asst.L.Karwan Abdulrahman Ali (Sulaimani Journal for Humanities, 2025)
Islam as a heavenly religion and the embodiment of the Kurdish majority, has an active participation in the life of Kurdish society, so this study aims to show the role of Islam as a main pole for the formation and strengthening of national identity Kurdish, with emphasis on the cultural, social and political dimensions of Kurdish life. The paper examines the relationship between religion and Kurdish national identity, by presenting how Islam has influenced the strengthening of social relations and maintaining the unity of Kurdish society, despite various challenges such as: foreign occupation and political division. Therefore, the study contributes to a deeper understanding of the relationship between religion and nationalism in multicultural societies. The research questions include: What role has Islam played in the revival of national thought and preservation of Kurdish identity? Why has the dominance of Islamic principles not been used to serve national identity? The research relies on analytical methodology; It combines historical research and analysis of Kurdish religious and political texts. The research plan also includes the following topics: Gateway: A brief discussion about Islam and Kurdish conversion to Islam Part 1: The role of Islamic culture in paying attention to the Kurdish nation and culture Part 2: Kurdish religious institutions and their role in preserving national identity Part 3: Islam between agreement or opposition to modern Kurdish nationalist discourse Part 4: A Contemporary Analysis of the Role of Islam in Shaping Kurdish National Identity in the Face of Challenges and Opportunities. In the end, the study has reached several conclusions, including: Islam has contributed to the preservation of Kurdish cultural identity, and in the past, Islam has not been used properly in the service of the Kurdish national issue and its new demands.
Keywords: Islam; Kurds; National Identity